The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.48077/scihor.24(8).2021.66-80
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Level of Products Novelty Importance for Developing Product Innovative Policy

Abstract: To substantiate the range of products of the enterprise there is a need to assess the potential of products in terms of the company’s ability to manufacture these products, consumer opportunities to meet their needs for these products, and market opportunities to ensure a strategic position among similar products. The study used structural-logical and causal methods of analysis to determine the structure of the novelty of goods. The numerical method of multi-criteria decision making TOPSIS (Technique for Order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…And yet, the reduction of R&D spending contributes to the insufficient level of innovation infrastructure development, the limitation of tools to support innovators, etc. Even though "the importance of innovation for the manufacturer means the conformity of the product to its innovative development strategy, determining its place on the market and prospects for further activity" (Fedulova et al, 2021), the indicated trends are also observed in the dynamics of changes in the number of innovative enterprises, which during 2016 -in 2018 they were 28.1%, and from 2018 to 2020 -8.5%, in the city of Kyiv there was a considerable reduction in their number -from 387 to 233 units. During this period, among innovative enterprises, a slight decrease occurred precisely among enterprises introducing new or significantly improved products, 1,899 and 1,832, respectively (State Statistics Service, 2022).…”
Section: Table 2 the Number Of Performers Of Randd Work In 2020 By Re...mentioning
confidence: 99%
“…And yet, the reduction of R&D spending contributes to the insufficient level of innovation infrastructure development, the limitation of tools to support innovators, etc. Even though "the importance of innovation for the manufacturer means the conformity of the product to its innovative development strategy, determining its place on the market and prospects for further activity" (Fedulova et al, 2021), the indicated trends are also observed in the dynamics of changes in the number of innovative enterprises, which during 2016 -in 2018 they were 28.1%, and from 2018 to 2020 -8.5%, in the city of Kyiv there was a considerable reduction in their number -from 387 to 233 units. During this period, among innovative enterprises, a slight decrease occurred precisely among enterprises introducing new or significantly improved products, 1,899 and 1,832, respectively (State Statistics Service, 2022).…”
Section: Table 2 the Number Of Performers Of Randd Work In 2020 By Re...mentioning
confidence: 99%
“…The issues of financing scientific research in the field of agricultural science are posed in the articles of Kazakhstani authors (Aimurzina et al, 2019;Kamenova et al, 2016), as a negative factor that does not allow ensuring competitiveness and the corresponding innovative and technological potential for the development of the agro-industrial complex of Kazakhstan (Fedulova et al, 2021). According to the researchers, the low level of funding for scientific research in the agroindustrial complex of Kazakhstan is a backbone factor in the low technological level of agriculture and low processing of agricultural products, which ultimately affects the food security of the country (Kniazevych et al, 2018;Taubayev et al, 2017).…”
Section: Introductionmentioning
confidence: 99%